Neonatal Screening for Leukocoria - Parveen Akhtar, Mariam Farooq, Sana Nadeem, B. A. Naeem (Pakistan Journal of Ophthalmology, 2014)
Purpose: To incorporate distant direct ophthalmoscopy for red reflex analysis to screen neonates for leukocoria and establish its importance. Material and Methods: A prospective study was conducted at Department of Pediatrics, Fauji Foundation Hospital, Rawalpindi, from February 2013 to September 2013. A total of 500 random neonates (newborns less than 28 days of age) were screened for leukocoria by distant direct ophthalmoscopy at 50 cm by means of a direct ophthalmoscope in dark conditions. The red reflex was compared between the two eyes and was classified into five categories: Red, orange, yellow, suspect / faint, and absent / leukocoria. The red reflex was compared to the gestational age, birth weight, oxygen therapy, phototherapy, and blood transfusion. Results: The results were tabulated and analyzed using SPSS version 17. The red reflex was analyzed and compared with neonatal variables (weight, gestational age, use of oxygen therapy, phototherapy and blood transfusion). The red reflex was found to be normal shades of red or orange in 495 neonates (990 eyes), with orange being predominant in 786 (78.6%) eyes, red in 204 (20.4%), yellow in 4 (0.4%), suspect / faint in 4 (0.4%), and absent / leukocoria in 2 (0.2%) eyes. Statistically significant association of the red reflex was found with oxygen therapy only (p = 0.000). Conclusion: Neonatal screening for red reflex assessment with distant direct ophthalmoscopy is essential for the early diagnosis and prompt management of ocular diseases causing leukocoria, which will subsequently prevent irreversible blindness, which is bound to occur if the diagnosis is delayed. Hence the importance of routine neonatal screening cannot be overemphasized. Key words: Neonatal, Red reflex analysis, Leukocoria